2016
DOI: 10.1111/zoj.12462
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of marine tardigrades from the northern coast of Portugal (Iberian Peninsula)

Abstract: Information about marine tardigrades in the Iberian Peninsula is very scarce. To improve our knowledge of this group, a sampling programme was started in 2010. The main coastal marine habitats of northern Portugal were explored. Eighteen species were found. Four species are new to science (the previously described Prostygarctus aculeatus Rubal, Veiga, Fontoura & Sousa-Pinto, 2013 and three species of the genus Batillipes), and another four species of the genera Batillipes, Echiniscoides, Halechiniscus and Wing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Therefore, these results suggest that the Portuguese coast is the occidental boundary for some Mediterranean tardigrade species. Additionally, Rubal et al (2016) also reported a new southern limit of B. tubernatis and S. haploceros Thulin, 1942 at the Portuguese coast. These boundary patterns suggested by the genera Batillipes and Styraconyx (i.e., southern limit for boreal and northern limit for warmer water species) is in agreement with observations on other marine groups such as macroalgae (Ardré 1971) or gastropods (Rubal et al 2013a).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Therefore, these results suggest that the Portuguese coast is the occidental boundary for some Mediterranean tardigrade species. Additionally, Rubal et al (2016) also reported a new southern limit of B. tubernatis and S. haploceros Thulin, 1942 at the Portuguese coast. These boundary patterns suggested by the genera Batillipes and Styraconyx (i.e., southern limit for boreal and northern limit for warmer water species) is in agreement with observations on other marine groups such as macroalgae (Ardré 1971) or gastropods (Rubal et al 2013a).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, this study confirms the particular biogeographical position of the Portuguese coast which is supported by the first record outside the Mediterranean Sea of B. adriaticus. Similarly, Rubal et al (2016) reported the first occurrence out of the Mediterranean Sea of Styraconyx sardiniae Group A D'Addabbo gallo, Morone De Lucia & de Zio grimaldi, 1989. Therefore, these results suggest that the Portuguese coast is the occidental boundary for some Mediterranean tardigrade species.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations